Collaborative capacity building for strengthening rehabilitation services in Sabah, Malaysia: a partnership between university hospital and state health department - Fatimah Ahmedy; Khin, Nyein Yin; Syahiskandar Sybil Shah; Sukhbheer Kaur Darsin Singh; Nurul Afiqah Fattin Amat; Frisca Aziah Francis; Yusof Ibrahim; Helen Lasimbang; Rosalam Sarbatly; Kasim Mansur; Candace Goh; Md. Feroz Kabir (Medical Journals Sweden AB, 2025)
Objective: This paper aims to outline the foundational framework for strengthening rehabilitation services in Sabah, Malaysia, through a collaborative capacity-building initiative between Hospital Universiti Malaysia Sabah (HUMS) and the Sabah State Health Department (JKNS). By focusing on academic, research, and service capacity-building, this partnership seeks to address the rehabilitation needs of the local population, particularly for individuals with functional limitations. Methods: The collaboration integrates HUMS’s academic and clinical strengths with JKNS’s existing rehabilitation services. Key components include developing postgraduate training for rehabilitation medicine, expanding community-based rehabilitation outreach services, and establishing a referral network between hospitals and community healthcare providers. Results: The partnership has resulted in the implementation of a comprehensive framework that enhances academic capacity, fosters research collaboration, and improves rehabilitation service delivery across Sabah. This approach is aligned with the WHO’s Rehabilitation 2030 initiative, advocating for stronger integration of rehabilitation into healthcare systems. Conclusion: The collaborative efforts between HUMS and JKNS demonstrate the critical role of partnerships between academic institutions and public health departments in strengthening rehabilitation services. This model offers a replicable strategy for influencing policy development and ensuring resource allocation to meet the growing rehabilitation needs in underserved regions.